How Proverbs Mean : Semantic Studies in English Proverbs. - Norrick, Neal R. (Berlin/Boston : De Gruyter, Inc., 1985)
No detailed description available for "How Proverbs Mean".
Intro -- Preface -- Chapter 1 Introduction -- 1.1 Aim and focus -- 1.2 Why study proverbs? -- 1.3 The corpus -- 1.4 Organization -- Chapter 2 Proverbs in texts and interactions -- 2.0 Introduction -- 2.1 How proverbs mean in texts -- 2.2 How proverbs mean in interactions -- 2.3 Summary -- Chapter 3 Defining the proverb -- 3.0 Introduction -- 3.1 Traditional proverb definitions -- 3.2 Structural proverb definitions -- 3.3 Supercultural versus ethnographic genre -- 3.4 Definition via feature matrix -- 3.5 A linguistically founded proverb definition -- Chapter 4 Literal proverb meaning -- 4.0 Introduction -- 4.1 Why literal readings for proverbs? -- 4.2 Ungrammatical proverbs -- 4.3 Summary -- Chapter 5 Figurative proverb meaning -- 5.0 Introduction -- 5.1 Research on proverbial figures -- 5.2 Synecdochic proverbs -- 5.3 Metaphoric proverbs -- 5.4 Metonymic proverbs -- 5.5 Hyperbolic proverbs -- 5.6 Paradoxical proverbs -- 5.7 Conclusions -- Chapter 6 The proverb inventory -- 6.0 Introduction -- 6.1 Inventory entries -- 6.2 Relations between entries -- Chapter 7 Conclusions and directions for research -- Appendix A: The annotated F-Corpus -- Appendix B: Proverbs in four Shakespearian plays -- Bibliography -- General Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Proverbs, English -- History and criticism; Proverbs -- History and criticism; Electronic books